Konsensualne formy działań administracyjnoprawnych zastępujące lub uzupełniające decyzje administracyjne - Kamiński, Marcin (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The study has been devoted to the issues of consensual forms of administrative-legal actions replacing or supplementing administrative decisions. The first part of considerations deals with the consensual forms which are the alternative legal forms of disposing of the administrative matters. The alternativity of these forms lies in the choice of the legal form of administrative matter disposing, the priority of using the consensual form and the subsidiarity of the administrative decision or in the legal possibility of replacing (substitution) the already issued decision with the consensual form. The second part of the analysis was focused on the normative solutions establishing the competence bases for the complementing or even concretizing of the administrative decision content by means of the consensual forms of the administrative authorities and private entities actions.